Hemolytic anemia following intravenous immunoglobulins in children with PIMS-TS: Two case reports - Sedlin, E.; Lau, S.; von Bernuth, H.; Kallinich, T.; Mayer, B. (Frontiers in Pediatrics, 2023)
This is the first case report on two children presenting with immediate and severe hemolytic anemia following the administration of high-dose intravenous immunoglobulins (IVIGs) in the context of pediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS). Hemolytic anemia was described as a significant decrease in hemoglobin and an increase in lactate dehydrogenase after the second administration of high-dose IVIGs was performed. Both patients were found to have AB blood group. One of our patients showed massive pallor, weakness, and inability to walk in association with hemolysis. However, in both cases, the anemia was self-limiting and transfusion of red blood cells was not required: both patients recovered without persistent impact. Nonetheless, we aim to draw attention to this widely unknown adverse effect of IVIG, especially in the context of PIMS-TS. We suggest determining the patient’s blood group prior to high-dose IVIG infusion and replacing the second IVIG through high-dose steroids or anticytokine therapy. Using IVIGs containing lower titers of specifically anti-A or anti-B antibodies to avoid isoagglutinin-caused hemolytic anemia is desirable; however, the information is not routinely available.